INTERCULTURAL ENGLISH TEACHING AND LEARNING TO YOUNG LEARNERS - Fauzi Miftakh (Universitas Negeri Padang, 2017)
Teaching of English now should also be incorporated with the intercultural knowledge of target language, including to young learners. It can make them aware of differences and similarities between their own culture and the culture of the target language. This study was a qualitative study which investigated how the intercultural teaching and learning was implemented to young learners in an English classroom in Karawang,West Java, Indonesia. The principles of Intercultural language teaching and learning proposed by Liddicoat & Scarino (2013) were used by the teacher in the activities. The data was taken by observing the teaching and learning process to 25 seventh grade students in the classroom that was done in four meetings and interviewing 6 sample of students to know their responses. The findings showed that the intercultural English teaching and learning provides more opportunities for young learners to be more active and critical toward other language and cultures as well as improve their English skills. Since they are still young, they still should be guided to understand the material well by the teacher. Finally, it is recommended to other teachers to implement intercultural English teaching and learning in teaching English to young learners.